Optimasi Pengaruh Konsentrasi Pelarut NaOH dan Ukuran Partikel Abu Pada Silica Dioksida (Sio2) dari Sekam Padi dengan Response Surface Methodology - Hardy, Krisna Jonata (Jurnal Serambi Engineering, 2025)
Silicon dioxide (SiO₂) is a high-value compound with various industrial applications, particularly as an adsorbent. Rice husk, an abundant agricultural byproduct, contains a high concentration of SiO₂, making it a promising alternative raw material. This study aims to determine the optimal conditions for silica extraction from rice husk ash using an alkaline extraction method. The variables examined were NaOH concentration (2, 3, 4, 5, and 6 M) and rice husk ash particle size (30, 50, 150, and 200 mesh). The response analysis focused on water absorption capacity, while process optimization was carried out using Response Surface Methodology (RSM). The results showed that the optimum condition was achieved at 4 M NaOH concentration and 100-mesh particle size. Under this condition, the obtained silica exhibited a water absorption capacity of 808.32 mg/g, indicating high SiO₂ quality as reflected by its optimal adsorption capacity. The RSM optimization confirmed the high validity of the model, with good agreement between experimental and predicted data, demonstrating that this method is effective and reliable for producing high-quality silica from rice husk waste.